Respuesta :

Answer: x-5

The expression x^2 - 25 can be written as x^2 - 5^2 since 5^2 = 25

5^2 = 5*5 =25

This is a difference of squares. The term x^2 is a perfect square and so is 5^2 = 25

Use the difference of squares factoring rule below

(a-b)(a+b) = a^2 - b^2

(x-b)(x+b) = x^2 - b^2 ... replace 'a' with 'x'

(x-5)(x+5) = x^2 - 5^2 .... replace b with 5

(x-5)(x+5) = x^2 - 25

So we see that x^2 - 25 factors into (x-5)(x+5). The x+5 is already written as the length, so that must mean the width is x-5